Management Thalassemia in Indonesia : A Literature Review - Friska Kamila Nabilasefanty; Pradana Zaky Romadhon (International Journal of Health and Medicine, 2025)
Thalassemia is a disease classified in the group of hereditary hemolytic anemia caused by the failure of the formation of one of the four amino acid chains forming Hb, causing incomplete Hb formation. Thalassemia carriers account for 7% of the world's population. At present, the cornerstone of treatment for β-TM in Indonesia remains supportive, including blood transfusions and iron chelation therapy. With a comprehensive discussion about thalassemia in Indonesia, it is hoped that the diagnosis and treatment of thalassemia will be more optimal and effective in future research.